Accounting information vs. financial market information in explaining stock returns: Evidence from publicly listed non-financial firms in the ASEAN-5 stock markets from 2010 to 2020 - Roque, Roseanne N. (Animo Repository, 2022)
In the presence of market inefficiencies, investors continue to heavily rely on public information from financial markets and financial statements in their investment decisions. Hence, the aim of this paper is to determine which between accounting information and financial market information explains stock returns better among publicly listed non-financial firms across the ASEAN-5 stock markets. The study covered the periods from 2010 to 2020. Through the panel data regression models, mainly the Fixed Effects Least Squares Dummy Variable (LSDV) models, results have shown that return on assets (ROA) and return on equity (ROE) are significant accounting information variables, while book-to-market (BM) ratio, dividend yield (DY), and market capitalization (MC) are significant variables of financial market information. Overall, both accounting information and financial market information can significantly explain stock returns. It was also found that the latter has greater explanatory power than the former after a comparison between their Adjusted R-squared values and Root Mean Square Error (RMSE), further strengthened by a t-test that indicates a significant difference within these values. Based on the findings of the study, recommendations were made to investors, business managers, regulatory bodies, and future researchers.